Effect of β-mannanase enzyme supplementation on the diet of broilers fed full-fat deactivated soy - Silva, Vitor Colossal da; Valentim, Jean Kaique; Araújo, Wagner Azis Garcia de; Silva, Bruno Alexander Nunes; Almeida, Alexander Alexandre de (Acta Scientiarum. Animal Sciences, 2024)
The objective of the present study was to evaluate the performance of broiler chickens fed a diet containing deactivated soy supplemented with the enzyme β-mannanase. A total of 1,152 broiler chickens, one day old and from the COOB 500 lineage, were used in a completely randomized design with a 4x2 factorial scheme. Four levels of β-mannanase (0, 80, 160, and 240 g ton-1) and the presence or absence of deactivated soy were tested, with eight repetitions, each with 18 birds per experimental unit. On the 1st, 7th, 14th, 21st, 28th, 35th, and 42nd days of life, the birds were weighed, and the feed leftovers were measured to obtain performance variables. From days 1 to 21, weight gain, feed conversion, and average weight were significantly affected by the addition of β-mannanase to the diet. The use of deactivated soy in combination with enzyme levels in mg kg-1 of metabolizable energy resulted in greater gains than did the use of soybean meal combined with the same levels of metabolizable energy. The use of deactivated soy along with 240 mg of β-mannanase enzyme supplementation in broiler diets from 1–42 days of age is recommended, as this supplementation improves bird performance.